Nordic approaches to international law - Kjeldgaard-Pedersen, Astrid (Brill Nijhoff, 2018)
"In August 2015, international legal scholars and expert practitioners from Denmark, Finland, Iceland, Norway, and Sweden gathered to discuss contemporary issues of international law from a Nordic perspective: Do the 'shared Nordic values' extend to embrace a common perspective on international law and policy beyond the Nordic region? And do international legal scholars in the Nordic countries share a professional outlook enabling us to speak of a distinct 'Nordic approach to international law'? This book contains a selection of the conference papers, which all address aspects of Nordic approaches to international law - varying significantly in terms of subject area, methodology and style. The book is relevant to international legal scholars in the Nordic countries and beyond"--